Pattern of Substance Abuse, Sexual Behavior and its Determinants among Unmarried Youth in India (Global Journal of Human-Social Science, 2015)
This paper describes patterns of substance abuse, sexual behaviour and its determinants among unmarried youth in India and also evaluates how these patterns are associated with each others. Data come from the Youth in India: Situation and Needs Study, a sub-nationally representative survey conducted during 2006-2008. Logistic regression analysis (binary and multinomial) showed relationships between predictor variables and alcohol consumption and alcohol and sexual risk indicators as well as two of the sexual health indicators associated with premarital sex. Substance use was significantly high among the age group of 20-24 years. Factors such as substance use by caste/tribe, any member in family, paid work, and lower educational status were significantly associated with substance use by study subjects. The prevalence of substance use was high among male youths as compared to female youths. Male youth recognized more Premarital sexual behavoiur than the female youth. Premarital sex were significantly higher among youths who had some disposable income in hand, i.e., those belonging the paid work or both paid and unpaid work.
Keywords: youth; substance use; alcohol; tobacco; sexual behaviour; sexual risk; sexual health